Unfavourable outcomes in orthognathic surgery - Krishnamurthy Bonanthaya; P Anantanarayanan (Indian Journal of Plastic Surgery)
Unfavourable outcomes are part and parcel of performing surgeries of any kind. Unfavourable outcomes are results of such work, which the patient and or the clinician does not like. This is an attempt to review various causes for unfavorable outcomes in orthognathic surgery and discuss them in detail. All causes for unfavorable outcomes may be classified as belonging to one of the following periods A) Pre- Treatment B) During treatment Pre-Treatment: In orthognathic surgery- as in any other discipline of surgery- which involves changes in both aesthetics and function, the patient motivation for seeking treatment is a very important input which may decide, whether the outcome is going to be favorable or not. Also, inputs in diagnosis and plan for treatment and its sequencing, involving the team of the surgeon and the orthodontist, will play a very important role in determining whether the outcome will be favorable. In other words, an unfavorable outcome may be predetermined even before the actual treatment process starts. During Treatment: Good treatment planning itself does not guarantee favorable results. The execution of the correct plan could go wrong at various stages which include, Pre-Surgical orthodontics, Intra and Post-Operative periods. A large number of these unfavorable outcomes are preventable, if attention is paid to detail while carrying out the treatment plan itself. Unfavorable outcomes in orthognathic surgery may be minimized If pitfalls are avoided both, at the time of treatment planning and execution.